Algal polysaccharides: new perspectives for the treatment of basal ganglia neurodegenerative diseases - Lucena, Alessandra Marinho Miranda; de Souza Lucena, Eudes Euler; Neto, Sebastião Pacheco Duque; Nobre, Leonardo Thiago Duarte Barreto; Rocha, Hugo Alexandre Oliveira; Câmara, Rafael Barros Gomes (Frontiers in Neuroanatomy, 2024)
The objective of this review was to verify the therapeutic effect of polysaccharides from algae against neurodegenerative disease models involving the basal ganglia. To achieve this, a literature search was conducted in the databases PubMed, Science Direct, Scopus, Web of Science, Embase, and Google Scholar. It was used the descriptors "neuroprotective or neural regenerative or immunomodulatory activity or neuroprotection" and "polysaccharide or carbohydrate or carbohydrate polymers" and "marine algae or seaweed" and "basal ganglia" according to the PRISMA methodology. This methodology included the steps of search, pre-selection, and inclusion of articles. A total of 737 hits were identified. After data analysis, 698 studies were excluded, resulting in a final sample 8 studies. Species such as Turbinaria decurrens, Gracilaria cornea, Chlorella pyrenoidosa, Arthrospira (Spirulina) platensis, Fucus vesiculosus, and Laminaria japonica demonstrated significant neuroprotective effects. This review suggests that polysaccharides derived from marine algae hold therapeutic potential in neuroprotection, modulation of inflammation, and amelioration of functional deficits. Their application in neurodegenerative disease models warrants further consideration.